Deposition of Poly(Ethylene Oxide)‐Like Plasma Polymers on Inner Surfaces of Cavities by Means of Atmospheric‐Pressure SDBD‐Based Jet. Issue 8 (2nd March 2016) - Gordeev, Ivan; Šimek, Milan; Prukner, Václav; Artemenko, Anna; Kousal, Jaroslav; Nikitin, Daniil; Choukourov, Andrei; Biederman, Hynek
Abstract : The jet of reactive effluents produced by surface dielectric barrier discharge was used to deposit PEO‐like plasma polymers from di(ethylene) glycol vinyl ether. The jet was confined within the hollow space of either circular cross‐section with substrate placed perpendicular to the jet, or rectangular cross‐section with the walls used as substrates. The best 67% retention of the ethers was obtained for the circular channel, whereas it was only 50% for the rectangular channel. In the latter case, deposition at longer distances was possible. In both cases, the deposition started with the formation of islands that grew, coalesced and eventually built up a continuous coating. Abstract : Several methods exist for preparation of non‐fouling coatings with excellent biocompatible properties . The deposition of such layers on the inner walls of different medical devices such as vascular grafts, catheters and for other biomedical applications is very important. This work demonstrates the possibility of using an SDBD‐based jet for deposition of PEO‐like plasma polymer onto the inner surface of narrow tubes.